Analisis Determinan Kebijakan Dividen pada Perusahaan Food And Drink yang Terdaftar di Bursa Efek Indonesia - Saroh, Lismai; Sriwardany, Sriwardany (Al-Buhuts, 2023)
This research aims to determine the influence of return on assets (ROA), current ratio (CR), company size, and leverage on dividend policy in food and drink companies listed on the Indonesia Stock Exchange in 2019-2022. The type of research in this research is quantitative. The population of this research is food and drink companies listed on the Indonesia Stock Exchange in 2019-2022, namely 60 companies. The sampling method uses a purposive sampling technique based on criteria, the number of samples used is 36 companies. The data analysis method uses multiple linear regression. Firstly, for Return On Assets (ROA), the tcount value is 2,210 > ttable (1.6955) (n-k=36-5=31), so there is a significant influence on the growth of Dividend Policy, secondly, for the Current Ratio, the tcount value is 1,587 < ttable (1.6955) ( n-k=36-5=31), then there is no significant influence on the growth of Dividend Policy. Third, on Leverage, the t-count value is 1.776 > ttable (1.6955) (n-k=36-5=31), so it has a significant influence on the growth of Dividend Policy, fourth. for Company Size, the tcount value is 1.869 > ttable (1.6955) (n-k=36-5=31), so there is a significant influence on the growth of Dividend Policy, and finally the influence of each variable simultaneously can be seen that the Fcount value (2.721) > Ftable (2.68) with a significance level of 0.002 < 0.05. So this shows that H4 is accepted as Return On Assets, Current Ratio, Leverage and Company Size, have a significant effect on Dividend Policy